The role of exosomes in multiple myeloma development & drug resistance - Menu, Eline (Henry Stewart Talks, 2018)
Introduction to the biology of Multiple Myeloma, The development of drug resistance in Myeloma, The role of the bone marrow environment in drug resistance, The concept of exosomes, Points of attention when dealing with exosomes, The role of exosomes within the bone marrow environment
Archived at 2025/09/30